2012
DOI: 10.1186/2049-6958-7-29
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of p53 and Ki67 expression in fiberoptic bronchial biopsies of patients with non small cell lung cancer

Abstract: BackgroundOverexpression of the tumor suppressor gene p53 and the marker for cellular proliferation Ki67 in open lung biopsies are indicated as predictor factors of survival of patients with lung cancer. However, the prognostic value of p53 and Ki67 in fiberoptic bronchial biopsies (FBB) has not been fully investigated. We evaluated p53 and Ki67 immunostaining in FBB from 19 with Non Small-Cell Lung Cancer (NSCLC: 12 adenocarcinomas, 5 squamous cell carcinomas and 2 NSCLC-NOS).MethodsFBB specimens were fixed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…In our study, the mean serum anti-p53 Ab level in stage I patients was found to be higher than that in other stages (Table 2), although not statistically significant. Ciancio et al (6) studied anti-p53 and anti-Ki-67 antibodies within specimens obtained by fiber-optic bronchial biopsies, and they reported that the prognosis was better in Ab-negative patients. Gomez et al (14) reported that p53 protein overexpression in lung adenocarcinoma correlated with lymphatic vessel invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the mean serum anti-p53 Ab level in stage I patients was found to be higher than that in other stages (Table 2), although not statistically significant. Ciancio et al (6) studied anti-p53 and anti-Ki-67 antibodies within specimens obtained by fiber-optic bronchial biopsies, and they reported that the prognosis was better in Ab-negative patients. Gomez et al (14) reported that p53 protein overexpression in lung adenocarcinoma correlated with lymphatic vessel invasion.…”
Section: Discussionmentioning
confidence: 99%
“…p53 is a tumor suppressor gene that plays an important role in controlling normal cell proliferation, and is located on the chromosome 17 (17p13.1). It is the most common target of genetic alteration in many tumors (6). Serum p53 protein is present in normal healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In lung cancer, several studies have reported that high Ki-67 expression was an indicator of poor prognosis in patients with non-small cell lung cancer (NSCLC) [4, 5]. However, few reports have evaluated Ki-67 expression in patients with small cell lung cancer (SCLC).…”
Section: Introductionmentioning
confidence: 99%
“…B 370: 20140228 suppressor gene [28]. Increased expression of this gene is recognized in a variety of cancers in humans and is also suggested as a possible prognostic marker in non-small cell lung cancer alongside Ki67 expression [29]. Similarly, p53 overexpression has been identified as a prognostic marker in canine mammary cancer [30].…”
Section: Aetiology Of Urogenital Carcinoma In the California Sea Lionmentioning
confidence: 99%